Knowledge and behavior changes in clinician after training of partnership for Diabetes Control in Indonesia. Issue 3 (May 2021) - Yunir, Em; Soewondo, Pradana; Soelistijo, Soebagijo Adi; Rudijanto, Achmad
Abstract: Background and aims: One of the main determinants of successful diabetes management is the quality of healthcare provider including general practitioner and internist which can be increased through medical training. This study aimed to describe the changes of clinician's knowledge and behavior of comprehensive diabetes management training program around Indonesia. Method: We conducted a three-day training program for general practitioners and internists for 3.5 years, 2013 to 2016. All clinicians invited as voluntary participant to send their patient data from medical record. Each participant was expected to submit a minimum of 25 type 2 diabetes (T2DM) set patient data before and 6 months after training program to analyze the impact of program in physician knowledge and behavior related to diabetes management. Result: 120 of 489 voluntary participants submitted completed baseline data with 4676 patient data. Meanwhile, only 32 participants that submitted completed data of 6 months before after training with 886 patient data. Most of parameters were improve before and after program. The greatest and lowest improvement were on A1c measurement (21%) and smoking assessment (2%). Conclusion: Intensive seminar and training was not enough to empower diabetes management. This research might push the creation of clinical practice program that were tailored to each care facilities and integrated within routine care aimed at continual improvement of its healthcare worker. Highlights: Diabetes training program for physician could improve quality management of diabetic. Great improvement after training were on A1c measurement, diabetes education, and triglyceride measurement. Parameters that decrease after training were antihypertensive therapy, A1c treatment, and blood pressure measurement.